Kurumlar vergisinde bölünme - Işıloğlu, Ebru (My University, 2009)
Şirketlerin kısmi ve tam bölünmesini incelediğimiz bu çalışmada, bölünme kavramı ile ticaret hukuku ve diğer hukuk dallarında kısmi ve tam bölünme usulü anlatılmıştır. Ticaret ortaklıklarının bölünme suretiyle yeniden yapılanmaları hukuki metinlerde düzenlenmiştir. Türk hukukunda kısmi bölünme konusunda maddi hukuk boşluğu bulunmaktadır. Türk Ticaret kanununda yer almayan bölünme müessesesi, ilk defa vergi kanunu ile Türk hukukunda ele alınmıştır. Ticaret ortaklıklarının bölünmesi, Adalet Bakanlığı nezdindeki Ticaret Kanunu Tasarısının yasalaşması ile maddi hukuk bakımından düzenlenmiş olacaktır. Ticaret hukuku boyutuyla şirketlerde kısmi ve tam bölünme, Anonim ve Limited Şirketlerin Kısmi Bölünme İşlemlerinin Usul ve Esaslarının Düzenlenmesi Hakkında Tebliğ, Ticaret Kanunu Tasarısı ve söz konusu tasarıya kaynaklık eden Avrupa Birliği mevzuatı, mehaz İsviçre hukuku ve Alman hukuku çerçevesinde değerlendirilmiştir. Kısmi bölünme hakkında vergi mevzuatı başta olmak üzere diğer hukuk dalları da ele alınmıştır. Türk hukukunda tüm bölünme çeşitlerinin maddi hukukta düzenlenmemesi, uygulamada anonim şirketlerin kısmi bölünmelerini engellememektedir. Kısmi bölünmeye ilişkin birleşmeye ilişkin ticaret kanunu hükümleri ve borçlar kanunundaki malvarlığı ve ticari işletmenin devri hükümleri ile kısmi bölünme işlemi gerçekleştirilebilir. Diğer taraftan Ticaret Kanunu Tasarısının yasalaşması ile bölünme müessesesi maddi hukuktaki yerini almış olacaktır. Tam Bölünme, Kısmi Bölünme, Şirketlerde Anonim Ortaklık

This thesis discusses the topic of partial and complete division. The discussion mainly evolves around the concept of division and the procedure of division, whether this be to a partial or complete extent, in other juristic branches. It has been published in legal drafts that as long as commercial partnerships division they will have the right to restructure again. There is a gap with regards to substantive law in cases of partial division in Turkish Law. The foundation of division which cannot be found in the Turkish Commercial Code has been taken into account for the first time in Turkish Law with its application within tax law. With regards to the division of the commercial partnership, once the draft of the Commercial Law is ruled as effective Law by the Ministry of Justice it will be organized within the context of substantive Law. The Declaration, Commercial Law draft and the source of the draft consisting of the European Union legislation required for the procedure and rudiments, has been prepared in the framework of the Swiss and German Law systems, in the scope of complete or partial division within Commercial Law, for the procedures of the partial division of Publicly Listed Companies and Limited Companies. With the partial division of tax legislation being the main subject area other legal branches have also been taken into account. As all types of division are organized within substantive law in Turkish Law some restrictions occurs with regards to partial division in Publicly Listed Companies. With regards to partial division partial combination, partial division can be carried out with commercial law arbitrament, the assets within code of obligations and periodic arbitraments of the commercial enterprise. On the other hand once the draft of the Commercial Law becomes effective Law the separating enterprise will take its place within substantive Law. Key terms: Complete division, partial division, Partnership with limited liabilities in companies
Keywords: Anonim Ortaklık; Kurumlar Vergisi; Mali Hukuk; Vergi Hukuku; Vergilendirme